DAYA TERIMA KONSUMEN TERHADAP HIDANGAN UTAMA DI KANTIN SEHATI SEKOLAH VOKASI IPB: Consumer's Acceptability to Main Dishes in The Sehati Canteen College of Vocational Studies IPB University - Ani Nuraeni; Lu'lu Ilmaknun (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2021)
ABSTRACTThe main purpose of this study is to examine the consumer's acceptability to the main dish in the Sehati Canteen College of Vocational Studies IPB University, by comparing the consumer's acceptability between chicken katsu and chicken teriyaki dishes served. Main course (main course) is a staple dish of a complete menu arrangement served at lunch anddinner,the portion size is larger than the appetizer (appetizer). The main course or main course of Japan consists of a bowl of rice(gohan), a bowl of miso soup(miso shiru),pickled vegetables(tsukemono) and fish or meat. Similar to in Indonesia, rice is a staple food of the Japanese people. The most popular Japanese main course among teenagers today is Chicken katsu and Chicken teriyaki. Chicken katsu is a famous dish from sakura country with the basic ingredients of chicken meat wrapped in flour so that the texture is crispy outside and soft inside. Chicken teriyaki is one of the typical Japanese food made from chicken breast in fillets and then diced or elongated, cooked with teriyaki sauce. Preparation to make the main course in the Sehati Canteen College of Vocational Studies IPB University consists of preparation of tools and preparation of ingredients. The main dish processing procedure is divided into staple food processing, animal side dishes and vegetable dishes. The preparation stage is done to make chicken katsu,chicken is reported before processing while at the preparatory stage of making chicken teriyaki,chicken, rice, and salad are reported in a ripe state. The main dish favorite test was conducted organoleptic test with panelists who came from healthy canteen consumers. Based on the results of the favorite test and the results of the output of statistical analysis obtained that the panelists prefer chicken katsu dishes in terms of appearance, color, taste, texture and shape compared to chicken teriyaki.